Conceptualizing Trust – Definitional Queries and its Role in Social Relations - Nafay Choudhury (University of Darussalam Gontor Press, 2023)
Purpose In this paper, I undertake a critical examination of the concept of trust to track its multiple valences and analyze the ways in which it facilitates interactions between various actors and the consolidation of social solidarity amongst groups of people. While a definition may be difficult to pin down with precision, certain salient characteristics may be identified. Trust may also be divided into personal trust between individuals known to one another and impersonal trust, which exist between strangers. Personal trust is often a function of ethnic and kinship networks where personal knowledge and common characteristics between people help consolidate social solidarity. Impersonal trust is often viewed as especially important in the move from simple to more complex and variegated societies. The various contours of trust can be illustrated through its interaction with the law, and law and trust are often viewed in opposition – on contracts with someone else specifically because they cannot trust them. Finally, trust may sometimes be hidden – or reinforced – by social hierarchies and relationships of power. This article explores these different angles of understanding the concept of trust, with the goal of enriching scholarly discussion surrounding the term and its role in maintaining social order in society.